Current Methods for the Discovery of New Active Ingredients from Natural Products for Cosmeceutical Applications - Espinosa-Leal, Claudia A.; Garcia-Lara, Silverio (Planta Medica, 2019)
Cosmeceuticals are designed to serve a dual purpose: to provide desired esthetical effects and to treat dermatological conditions. Natural products derived from plants and marine organisms are a novel source of potential cosmeceutical active ingredients for incorporation into new formulations due to consumer demands. Contrary to common perceptions, most regulatory agencies do not view cosmeceuticals as being a separate category from cosmetics; thus, these products are not regulated accordingly, thereby forcing the consumer to rely on the self-regulatory policies of the cosmetics industry. Cosmeceuticals are advertised as having capabilities that include anti-aging, anti-acne, solar-protective, wound healing, and skin whitening. Such traits normally comprise several biological activities. In order to ensure the safety and efficacy of these products, active ingredients employed in the formulations must undergo a series of tests. In this review, in vitro (enzymatic and cellular) and in vivo tests employed to evaluate the potential of new cosmeceutical active ingredients are discussed, and new trends that are being explored by the cosmeceutical industry are described.
Keywords: bioactivity; natural products; cosmeceuticals; toxicity; in vitro tests; active ingredient